PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SARANA PRASARANA TERHADAP KINERJA GURU SMP NEGERI KOTA SEMARANG - Eko Djatmiko (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
The less maximum performance of teachers of State Junior High Schools in Semarang Municipality is not only because of their ranks, but is also effected by little understanding of the principals on the conditions of teachers nd administrative staffs. Clean, beautiful, and comfortable classrooms and other educational facilities also influence the teachers' performance.This study deals with the effect of the principal's leadership and facilities on the teachers' performance of State Junior High Schools Semarang Municipality. The problems are formulated as follows: (1) to what extent is the effect of the principal's leadership on the teachers' performance of State Junior High Schools of Semarang Municipality, (2) to what extent is the effect of facilitieson the teachers' performance of State Junior High Schools of Semarang Municipality, (3) to what extent is the effect of both the principal's leadership and facilities on the teachers' performance of State Junior High Schools of Semarang Municipality.Two models of regression analysis, simple regression and multiple regression are used in this study. The simple regression analysis is used to analyze the effect of the principal's leadership as the independent variable on the teachers' performance as the dependent variable, and the effect of the facilities as the independent variable on the teachers' performance as the dependent variable.The Multiple regression analysis is used to analyze the effect of both the principal's leadership and facilities on the teachers' performance. The sample consists of 35 schools selected by the use of a proportional stratified random sampling technique and the data are collected by the use of questionnaires.The results of the descriptive analysis show that the principal's leadership of State Junior High Schools of Semarang Municipality is categorized as good. The facilities and the teachers' performance of State Junior High Schools of Semarang Municipality are also classified as good.The findings of the study show that the principal's leadership and the facilities partially significantly the teachers' performance of State Junior High Schools of Semarang Municipality, indicated by the result of the ttest. In addition, the principal's leadership and facilities simultaneously affect significantly the teachers' performance, indicated by the result of the Ftest.